The isolation effect when offloading memory - Kelly, Megan O.; Risko, Evan F. (Elsevier, 2019)
Offloading is a widespread and vital strategy for remembering. Yet, we lack a deep understanding of the mechanisms involved during the offloading of to-be-remembered information. One hypothesis is that offloading information is associated with a reduced engagement of top-down mnemonic strategies. A resulting prediction is that phenomena not solely by-products of such mechanisms should remain during offloading. We tested this prediction using the isolation effect (when recall is better for distinct items relative to nondistinct items). Participants had to remember lists of items (words) and, in most cases, were told that they could rely on an external store. On one trial, this expectation was violated, and participants had to unexpectedly rely on their internal/biological memory. Consistent with the prediction, results demonstrate a robust isolation effect irrespective of whether individuals could offload. The findings suggest that memory for distinct events is less susceptible to the typical cost of offloading to-be-remembered information.
©American Psychological Association, 2019. This paper is not the copy of record and may not exactly replicate the authoritative document published in the APA journal. The final article is available, upon publication, at: https://doi.org/10.1037/h0101842
Keywords: cognitive offloading; isolation effect; distinctiveness